The rate of mental health service use in New Zealand as analysed by ethnicity. (June 2018) - Tapsell, Rees; Hallett, Charlene; Mellsop, Graham
Objectives: To compare by ethnicity the rates of apparent new referrals and admissions to mental health services for selected major diagnostic groupings. Method: Using a Ministry of Health database covering all referrals and admissions to New Zealand's Mental Health services in 2014 and who had not been patients in the preceding six years, population adjusted rates of presentation were calculated and compared across the two major New Zealand ethnic groupings. Results: Population corrected rates of apparently new cases of schizophrenia are more than twice as common in Māori as in non-Māori. Major depression is also significantly more common in Māori. That same trend was not evident for bipolar patients. Conclusions: These ethnically associated apparent differences in the rates of schizophrenia and depression need both confirmation and explanation.